(untitled) (Ágora Journal, 2020)
This article intends to present the captive family of Itapemirim in the final years of slavery (1872-1888). The time frame was made between the enactment of two important laws: the Free Womb Law, which freed those born with a captive belly after that date, and the Golden Law, which ended slavery. The sources used in this research were the notary (post mortem inventories and wills) and the ecclesiastical (baptism book). These documents reveal the existence of the captive family of Itapemirim, which in the analyzed period was consolidated in the region. Most families were matrilinear, some with few and others with many children. There is also the presence of many Africans, even decades after the end of the international traffic in souls.